High-dimensional spectral flow cytometry of activation and phagocytosis by peripheral human polymorphonuclear leukocytes - Lamb, Evan R; Glomski, Ian J; Harper, Taylor A; Solga, Michael D; Criss, Alison K (Journal of leukocyte biology, 2025)
Polymorphonuclear leukocytes (PMNs) are terminally differentiated phagocytes with pivotal roles in infection, inflammation, tissue injury, and resolution. PMNs display a breadth of responses to diverse endogenous and exogenous stimuli, making understanding of these innate immune responders vital yet challenging to achieve. Here, we report a 22-color spectral flow cytometry panel to profile primary human PMNs for surface marker expression of activation, degranulation, phagocytosis, migration, chemotaxis, and interaction with fluorescently labeled cargo. We demonstrate the surface marker response of PMNs to phorbol ester stimulation compared with untreated controls in an adherent PMN model with additional analysis of intra- and inter-subject variability. PMNs challenged with the Gram-negative bacterial pathogen Neisseria gonorrhoeae revealed infectious dose-dependent changes in surface marker expression in bulk, population-level analysis. Imaging flow cytometry complemented spectral cytometry, demonstrating that fluorescence signal from labeled bacteria corresponded with bacterial burden on a per-cell basis. Spectral flow cytometry subsequently identified surface markers, which varied with direct PMN-bacterium association as well as those which varied in the presence of bacteria but without phagocytosis. This spectral panel protocol highlights best practices for efficient customization and is compatible with downstream approaches such as spectral cell sorting and single-cell RNA-sequencing for applicability to diverse research questions in the field of PMN biology.